Recuperation mechanism of direct taxation to control post covid economic contraction: India’s new tax reform with crypto tax - Khan, Ruby (Journal of Accounting, Business and Finance Research, 2024)
This study explores the impact of the progressive tax structure on income equality, emphasizing the significance of direct taxes in promoting economic and social equality. It also examines the challenges faced by the Indian government in meeting its revenue targets due to the decline in corporation tax and personal income tax revenues. The present study assesses the role of the newly implemented tax by the Indian Finance Ministry on capital gains from the sale or purchase of cryptocurrencies and its impact on economic growth. A qualitative approach has been adopted, utilizing secondary information sources for characterization and analysis. The study relies on Time Series Data from the Income Tax Department for the financial years 2000-01 to 2018-19 and global estimates of total tax revenues published by the International Centre for Tax and Development (ICTD). The findings indicate that the substantial decline in direct tax revenues necessitated a search for alternative sources of income. The separate taxation system for cryptocurrencies has legitimized digital assets and enabled the government to monitor transactions and capital gains. The introduction of the "Digital Rupee" aims to enhance the digital economy through efficient currency management. This research highlights the need for policymakers to develop a well-defined regulatory framework for cryptocurrency taxation. Clear regulations on cryptocurrency taxation and the "Digital Rupee" could help India boost its digital economy while ensuring better monitoring of crypto transactions and revenues.